(untitled) (Research, Society and Development, 2022)
Bayesian Belief Networks (BBN) modeling the water quality has become popular due to advances in computational techniques. For this instance, BBN is a useful tool to modeling the relationship between water quality data and population or urbanization parameters on a watershed scale. This method can combine primary water quality data and decision parameters and help scientists and decision-makers analyze several scenarios on a watershed, including the effect of scale. This paper aims to analyze and discuss the application of Bayesian Belief Network (BBN) on the relationship between watershed water quality and sanitary management indicators, studying a case on the Pantanal Wetland tributary watershed. Two scales BBN were constructed using ten years of water quality and sewage management datasets. Both BBNs were responsive and sensitive to water quality parameters. The Total Nitrogen and E. coli were de most essential parameters to simulate changes in water quality scenarios. The simulated scenarios showed structural limitations about the Pantanal Wetland Cities’ sanitary system in the present study. We strongly recommend a review of the goals of sanitary structure and services and alert to the risk of a sanitary crisis in Pantanal Wetland.